Properties of aluminium oxide in nanofluids / Roslan A. ... [et al.] - Roslan, A; Mohamad Shafie, D.M; Mohd Rizal, S.S; Jamarullaili, N.H.A (2018)
This paper contains the research is to study what is the effect of aluminium oxide to the mixture of ethylene glycol and ultrapure water. Nanofluids are a fluid for instance oil or water containing nanometer-sized particles. These nanoparticles are usually metal oxides. The objective of this research is to study the properties of aluminium oxide on ethylene glycol-ultrapure water to determine the specific heat capacity, freezing point and thermal conductivity. For sample preparation aluminium oxide powder measured in different masses for each sample by using an analytical balance. For sample 0.001, 397.4 mg of aluminium oxide powder, 795.4 mg for sample 0.002, 1194.58 mg for sample 0.003, 1594.38 mg for sample 0.004 and 1994.97 mg for sample 0.005. The experiment for specific heat capacity was conducted using differential scanning calorimetry, Perkin Elmer DSC6000 and each sample using specific amount which is 10mg. Hence, high concentration of nanoparticles gives high value of specific heat capacity. For the freezing point determination, the experiment was also conducted using differential scanning calorimetry, Perkin Elmer DSC6000. 10 mg of the mixture is taken for this experiment which resulting 0.003 as the best sample since the freezing point of this sample fulfill the requirement for the coolant. Lastly, for thermal conductivity, the samples were arranged in test tubes include radiator coolant and ethylene glycol with water in test tube rack. The test tube rack is soaked in the water bath until it reaches the set temperature. The sample is taken 3 times using KD-2 PRO probe to achieve average result and the best sample was 0.003. To be concluded, the volume fraction of 0.003 indicate best result because the results achieved the standard desired for thermal conductivity and specific heat capacity